Medication Errors in Pediatrics: Proposals to Improve the Quality and Safety of Care Through Clinical Risk Management - D'Errico, Stefano; Zanon, Martina; Radaelli, Davide; Padovano, Martina; Santurro, Alessandro; Scopetti, Matteo; Frati, Paola; Fineschi, Vittorio (Frontiers in Medicine, 2022)
Medication errors represent one of the most common causes of adverse events in pediatrics and are widely reported in the literature. Despite the awareness that children are at increased risk for medication errors, little is known about the real incidence of the phenomenon. Most studies have focused on prescription, although medication errors also include transcription, dispensing, dosage, administration, and certification errors. Known risk factors for therapeutic errors include parenteral infusions, oral fluid administration, and tablet splitting, as well as the off-label use of drugs with dosages taken from adult literature. Emergency Departments and Intensive Care Units constitute the care areas mainly affected by the phenomenon in the hospital setting. The present paper aims to identify the risk profiles in pediatric therapy to outline adequate preventive strategies. Precisely, through the analysis of the available evidence, solutions such as standardization of recommended doses for children, electronic prescribing, targeted training of healthcare professionals, and implementation of reporting systems will be indicated for the prevention of medication errors.